COVID Arm After Moderna Booster in Healthcare Worker: A Case Report - Anshari Saifuddin; Sukamto Koesnoe; Nia Kurniati; Sondang Sirait; Riesye Arisanty; Evy Yunihastuti (Acta Medica Indonesiana)
SARS CoV-2 virus has infected more than 200 million people worldwide and more than 4.4 million in Indonesia. The vaccination program has become one of the solutions launched by many countries globally, including Indonesia, to reduce the transmission rate of COVID-19. Various vaccination platforms are produced, such as inactivated, viral vector, mRNA, and protein subunit. The vaccination booster program with mRNA platform (Moderna) was launched by the Indonesian government to give better protection for health care workers, particularly from delta variant. In this case report, we discuss one of the typical side effects of Moderna vaccine, which is referred to as the COVID arm.